The Democracy reader classic and modern speeches, essays, poems, declarations, and documents on freedom and human rights worldwide - Ravitch, Diane; Thernstrom, Abigail M. 1936- (New York HarperCollins, 1992)
Classic and modern speeches, essays, poems, declarations, and documents on freedom and human rights worldwide--Subtitle.
Classical and European thought -- The Peloponnesian war / Thucydides -- The republic / Plato -- The politics / Aristotle -- Summa Theologica / Thomas Aquinas -- The dicourses / Niccolo Macciaveli -- Areopagitica / John Milton -- Leviathan / Thomas Hobbes -- A letter concerning toleration -- Second treatise of civil government / John Locke -- The spirit of laws / Charles De Montesquieu -- Discourse on the origin and foundations of inequality / Jean-Jacques Rousseau -- On election to parliament -- Letter to the sheriffs of Bristol / Edmund Burke -- The declaration of the rights of man and citizen / National Assembly of France -- The liberty of the ancients compared with that of the moderns / Benjamin Constant -- Jewish disabilities / Thomas Babington Macaulay -- The prelude / William Wordsworth -- On liberty -- The subjection of women / John Stuart Mill -- The English Constitution / Walter Bagehot -- Beyond good and evil / Friedrich Nietzsche -- September 1, 1939 / W.H. Auden -- England, your England / George Orwell -- The iron curtain / Winston Churchill -- Two concepts of liberty / Isaiah Berlin -- On human conduct / Michael Oakeshott -- The American experience -- Massachusetts body of liberties -- The Declaration of Independence -- Notes on the state of Virginia-religion -- What I like and don't -- On the Bill of Rights -- First inaugural adddress / Thomas Jefferson -- Corresondence on women's rights / Abigail and John Adams -- Virginia Bill of Rights / George Mason -- Massachusetts slave petition -- Speech at the Constitutional Convention / Benjamin Franklin -- The Constitution of the United States of America -- The Federalsit No. 9,10,39,51,70 / Alexander Hamilton, James Madison and John Jay -- Farewell address / George Washington -- Marbury v. Madison / John Marshall -- Proclamation on nullification / Andrew Jackson -- Democracy in America / Alexis De Tocqueville -- Introduction to democratic review -- Seneca Falls Declaration of Sentiments and Resolutions -- Civil Disobedience / Henery David Thoreau -- Speech at Peoria -- First inaugural address -- Gettysburg Address / Abraham Lincoln -- South Carolina secession statement -- Women's right to vote / Susan B. Anthony -- Address to the American Missionary Association / Frederick Douglass -- Dissent from Plessy v. Ferguson / John Marshall Harlan -- Dissent from Abrams v. United States / Oliver Wendell Holmes -- Bread and freedom / Sidney Hook -- The four freedoms / Franklin Delano Roosevelt -- West Virginia Board of Education v. Barnette / Robert H. Jackson -- Stride toward freedom -- Letter from Birmingham city jail / Martin Luther King, Jr. -- Contemporary international democratic ideas -- International Declaration of Human Rights -- Nobel Prize / Boris Pasternak -- Live not by lies / Aleksandr Solzhenitsyn -- Peace, progress, and human rights / Andrei Sakharov -- Why must we be grateful? / Sergei Grigoryants -- The official Polish press on the events of March 1968 / Jakub Karpinski -- The right to historical truth / Adolf Juzwenko -- What does the political scientist know? / Artur Miedzyrzecki -- Report from the besieged city -- The power of taste / Zbigniew Herbert -- Nobel Peace Prize lecture / Lech Walesa -- Charter 77 Declaration -- The power of the powerless -- New Year's address / Vaclav Havel -- A few remarks -- The reburiel of Imre Nagy / Viktor Orban -- Romania: the grim island of South-Eastern Europe / Helmut Frauendorfer -- A star in my street / Ana Blandiana -- Rejecting hatred / Vytautas Landsbergis -- The fifth moderization / Wei Jingsheng -- Trial of Wei Jingsheng -- The answer -- Declaration / Bei Dao -- Appeal to Deng Xiaoping / Fang Lizhe -- The May 19 petition -- Poems from Tiananmen square -- Statement of the Federation for a Democratic China -- Human rights in China / Fang Lizhe -- The dream of a people -- I am a child of Burma / Nyein Chan -- Ape and man / Nguyen Chi Thien -- In good faith / Salman Rushdie -- Statement at the Rivonia trial / Nelson Mandela -- An open letter to citizen Mobutu Sese Seko -- The universitality of basic rights / Gibson Kamau Kuria -- Protest against his arrest / Gitobu Imanyara -- Today the Somalis, tomorrow ... / Mweni Mwangeka -- 200 vs. 20,000,000 / Mwelu Mutuku -- Religion and human rights / Wole Soyinka -- Testimony of an ex-censor / Anonymous -- Memoir of terror / Nabil Janabi -- The roots -- Separation / Sherko Bekas -- In defense of free speech / Luis Aguilar -- Poems of the Cuban revolution / Herberto Padilla -- Press conference / Mauricio Redoles -- Latin American and democracy / Octavio Paz -- Latin America: the democratic option / Mario Vargas Llosa -- The charter of Paris for a new Europe -- Bloody Sunday in Vilnius / Moscow News Board of Directors.
Includes bibliographical references and indexes.
Also issued online.
Keywords: Democracy -- History